Report of the Steering Committee on Agriculture and Allied Sectors for the Tenth Five Year Plan - Planning Commission (Planning Commission, Government of India, 2002)
The Report of the Steering Committee on Agriculture and Allied Sectors for the Tenth Five Year Plan, chaired by M. S. Swaminathan under the aegis of the Planning Commission, outlines a comprehensive roadmap for revitalizing Indian agriculture to ensure food, livelihood, ecological, and national security. Recognizing agriculture as the backbone of rural livelihoods and a critical contributor to GDP, the report reviews past achievements, including the transformative impact of the Green Revolution driven by high-yielding varieties and institutional research support from bodies such as the Indian Council of Agricultural Research, while cautioning against deceleration in productivity growth during the 1990s. It emphasizes the urgent need for technological and managerial upgradation, diversification into horticulture, animal husbandry, dairying and fisheries, integrated natural resource management, organic farming zones, disease-free livestock zones, and strengthened agricultural infrastructure including irrigation, storage, and marketing systems. The report proposes a National Mission for Farmers’ Well-being, convergence of technology missions, bridging regional imbalances, empowering smallholders through value addition and agro-processing, and establishing a National Grid of Community Food Banks to realize the vision of a hunger-free India inspired by Mahatma Gandhi. Stressing institutional reforms in research, education, extension, credit, and cooperative structures, the Steering Committee advocates maximizing existing institutional capacities rather than proliferating new structures, with the overarching goal of achieving an “evergreen revolution” that combines productivity growth with sustainability, equity, and improved quality of life for farm families.
Government of India Planning Commission January - 2002
Keywords: Agricultural Development; Evergreen Revolution; National Mission For Farmers; Food Security; Green Revolution; Integrated Natural Resource Management; Agricultural Research And Education; Horticulture Development; Animal Husbandry And Fisheries; Organic Farming Zones; Agricultural Infrastructure; Tenth Five Year Plan